The Processing of Phi-features in Sentences with Third-person Pronoun: An ERP Study in Turkish - Mehmet AYGÜNEŞ (Dilbilim Araştırmaları Dergisi)
The relationship between Person and Number features is often addressed in both theoretical and experimental studies. It is noteworthy that the discussion on how these features are processed has evolved over time towards how Person and Number features are structured in constructions with different persons (first person, second person, third person). While some studies state that Person and Number features can only be tested with third-person sentences (Manchini et al., 2011; Mancini et al., 2014), other studies state that these features can be tested with all person pronouns except R-expressions (regular noun phrases) (Ackema & Neeleman, 2019). In the literature, it is noteworthy that the relationship between the processing of Person and Number features has been tested with first- and second-person pronouns and R-expressions, but there is no study testing the issue with third-person pronouns. The aim of this study was to investigate whether there is a difference in the processing of Person and Number features in sentences with third-person pronouns in Turkish using Event-related Brain Potentials (ERPs). In this study, three conditions, namely Grammatical, Person Mismatch and Number Mismatch, were presented visually in words to 33 participants. In the study, a widespread N400 component was observed in both the processing of the Person feature and the processing of the Number feature. It was found that there was no difference between the two features in the corresponding time window. However, in the next time window, a late N400 component was observed in the processing of the Number feature, while a positivity (P600) was observed in the processing of the Person feature. In this time window, there is a difference in the processing of the Person and Number features. In conclusion, this study found that there is a difference in the processing of the Person and Number features in sentences with third-person pronouns in Turkish. It is suggested that the P600 finding in the processing of the Person feature reflects the difficulty in processing this feature. It is suggested that the late N400 finding in the processing of the Number feature may be due to the load it imposes on the processing process due to the fact that the morphological appearance of the Number feature in verb conjugation is parallel to nominal pluralisation, and the greater demand on working memory as the resolution of the Number mismatch involves more alternatives than the Person mismatch.